Analysis of submarine steering: effects of cognitive and perceptual–motor requirements on the mental workload and performance of helmsmen. Issue 4 (November 2016) - Philippe, Rauffet; Christine, Chauvin; Chiara, Nistico; Samantha, Judas; Toumelin, Norbert
Abstract The purpose of the study is to model manual submarine steering and its effects on helmsmen in terms of performance and mental workload. This activity is first formalized according to (a) cognitive requirements, by identifying different levels of control, and (b) perceptual–motor requirements, by analysing the directional compatibility of control–display design. An experiment is then carried out on a simulator designed by a world leader in military naval shipbuilding. This experiment follows a unique scenario including two driving situations with different levels of cognitive requirements (approach and stabilization phases). It is achieved by two groups, each carrying out a perceptual–motor task on a specific steering control–display configuration proposed by the naval shipbuilder (one with a standard numeric display and one with a new visual–spatial representation, both tasks controlled by the same joystick). The findings of this study show that the cognitive requirements during the stabilization phase with high propulsion speed produce increased mental workload, and the perceptual–motor requirements also produce increased mental workload when a direction-of-motion stereotype is violated (upward–forward relationship).